2007
DOI: 10.1002/app.26936
|View full text |Cite
|
Sign up to set email alerts
|

Development of high‐absorbent light‐weight sanitary napkin

Abstract: This article presents a method of preparing the absorbent core for an ultrathin sanitary napkin using super absorbent fiber (SAF) and viscose fiber blends with varying SAF percentages and mass per unit area (g/m2). The SAF/viscose blended carded webs were sandwiched between two layers of nonwoven fabric to integrate and encapsulate it. The prepared napkin samples showed significantly better rates of absorption for saline solution even though the glass tube wicking (gravimetric) test gave only comparable result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 3 publications
(2 reference statements)
0
15
0
Order By: Relevance
“…The liquid spreading length was found to be predicted reasonably well by the model developed by Kim and Pourdeyhimi (2003) based on the expression given for the directional permeability by Mao and Russel (2000). Das et al (2008) reported a method of preparation of an absorbent core for ultrathin sanitary napkins using blends of superabsorbent fi bres and viscose fi bres. The superabsorbent/viscose fi bre blended carded webs were sandwiched between two layers of nonwoven fabrics, one made of parallel-laid viscose fi bres and the other prepared from random laid viscose fi bres.…”
Section: Liquid Sorption Characteristics Of Composite Nonwovensmentioning
confidence: 92%
“…The liquid spreading length was found to be predicted reasonably well by the model developed by Kim and Pourdeyhimi (2003) based on the expression given for the directional permeability by Mao and Russel (2000). Das et al (2008) reported a method of preparation of an absorbent core for ultrathin sanitary napkins using blends of superabsorbent fi bres and viscose fi bres. The superabsorbent/viscose fi bre blended carded webs were sandwiched between two layers of nonwoven fabrics, one made of parallel-laid viscose fi bres and the other prepared from random laid viscose fi bres.…”
Section: Liquid Sorption Characteristics Of Composite Nonwovensmentioning
confidence: 92%
“…[1][2][3] Superabsorbents are particular 3-D network hydrophilic functional polymer materials which can absorb and hold huge volume of aqueous liquids but do not dissolve. Owing to the unique advantages, superabsorbents have found extensive application in various fields such as agriculture, 4,5 hygienic products, 6 wastewater treatment, 7-9 dehydrating agent 10 and drugdelivery systems, [11][12][13] etc. Currently, most of the superabsorbents used in practice are petroleum-based synthetic polymer with high production cost and poor environmental friendly properties, 14 and thus new types of multi-component superabsorbents derived from naturally available polysaccharides and facile synthesis methods are desired.…”
Section: Introductionmentioning
confidence: 99%
“…(4). 37 δ mix = δ 1 ψ 1 + δ 2 ψ 2 (4) where ψ 1 and ψ 2 are the volume fraction for the two components, and δ 1 and δ 2 are the solubility parameters of each component. The δ values of methanol, acetone, DMSO, ethylene glycol and glycerol are 14.5, 9.9, 14.5, 14.6 and 16.5 (cal/cm 3 ) 1/2 , respectively, which is clearly smaller than 23.4 of water.…”
Section: Resultsmentioning
confidence: 99%
“…1 By virtue of the unique advantages, hydrogels become one of the upcoming classes of polymerbased materials and have found extensive applications in many fields, such as water-saving materials for agriculture, 2,3 hygienic products, 4 drug-delivery systems, 5-7 wastewater treatment, [8][9][10][11][12] dehydrating agent, 13 tissue engineering, 14 and biosensor, 15 etc. Thus far, numerous hydrogel materials have been developed by using various raw materials and methods.…”
Section: Introductionmentioning
confidence: 99%